Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2001
DOI: 10.2143/ac.56.2.2005624
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular risk factor levels in Portuguese students

Abstract: The prevalence of cardiovascular risk factors is high among young male Portuguese students and preventive measures should be applied, namely regarding obesity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
1
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 0 publications
5
1
0
1
Order By: Relevance
“…In the same population, we have also found that the prevalence of high blood pressure was higher, although not significantly, in girls than in boys. Systolic blood pressure showed a positive correlation with increased age among Age (years) Figure 2) Age-specific percentiles (fifth, 10th, 25th, 50th, 75th, 90th and 95th percentiles in ascending order) of diastolic blood pressure measurements in urban school children in Sousse, Tunisia boys, consistent with findings reported by several other studies of children (26)(27)(28). The negative correlation found between systolic blood pressure and age among girls could be explained by the hormonal modifications related to puberty, which starts earlier among girls than among boys.…”
Section: Discussionsupporting
confidence: 88%
“…In the same population, we have also found that the prevalence of high blood pressure was higher, although not significantly, in girls than in boys. Systolic blood pressure showed a positive correlation with increased age among Age (years) Figure 2) Age-specific percentiles (fifth, 10th, 25th, 50th, 75th, 90th and 95th percentiles in ascending order) of diastolic blood pressure measurements in urban school children in Sousse, Tunisia boys, consistent with findings reported by several other studies of children (26)(27)(28). The negative correlation found between systolic blood pressure and age among girls could be explained by the hormonal modifications related to puberty, which starts earlier among girls than among boys.…”
Section: Discussionsupporting
confidence: 88%
“…Higher incidence of hypertension in men in our study was primarily driven by the 12.7 mmHg difference of SBP values between genders, which is in accordance with data from other studies [11, 16, 19]. …”
Section: Discussionsupporting
confidence: 93%
“…It is worth mentioning that a similar, relatively high incidence of hypertension in adolescents, especially males (6.8-23%, compared to 1.5-6% in females), was reported by authors from other European countries [11, 14, 16] and former Polish studies [17, 18], although the last two presented some methodological drawbacks.…”
Section: Discussionsupporting
confidence: 57%
“…The gender-related differences in systolic blood pressure have been published by several authors [14,37,38]. In the literature there are also studies using criteria other than those we used to evaluate hypertension [16], e.g.…”
Section: Discussionmentioning
confidence: 99%